Indonesia's Economic Diplomacy in Increasing Halal Product Exports through the Organization of Islamic Cooperation (2020-2024) - Qolby, Annisa Syifa; Astuti, Wiwiek Rukmi Dwi (Insignia: Journal of International Relations, 2024)
Indonesia has ambitions to become the center of the world's halal products because of its potential in the halal industry, especially in the food sector. However, currently Indonesia is still only the main destination for other countries' halal product markets when Indonesia should be a major player in the world halal industry. This can be seen in 2020, a gap between the export value of Indonesia's halal products in OIC and the value of import needs for halal products. The OIC, which is the largest Muslim majority group, has great potential as a non-traditional market for the export of Indonesian products. This research aims to find out how economic diplomacy is carried out by Indonesia in increasing exports of halal products through the OIC. Descriptive qualitative research methods are used to collect and analyze data that has been collected regarding economic diplomacy carried out by Indonesia to increase exports of halal products through the OIC. The results of this study show that Indonesia's economic diplomacy has been carried out through product promotion, meetings with relevant stakeholders, and bilateral agreements between Indonesia and OIC member countries. Indonesia cooperates directly with organizations under the OIC such as COMCEC, ICDT, and SMIIC. The form of Indonesia's economic diplomacy that has been maximized well is through product promotion and Indonesia's participation in various forums held by organizations under the OIC, such as discussion forums, seminars, and workshops. As for agreements and negotiations, they are still not fully implemented properly due to several articles in the agreement that are still in the status of further discussion and have not been fully implemented.